Process optimisation and quality evaluation of fruit pulp based yoghurts - Lovely Mariya Johny (Department of Community Science, College of Horticulture, 2019)
Yoghurt is a coagulated milk product that results from the fermentation of lactose in milk by Lactobacillus bulgaricus and Streptococcus thermophilus. Yoghurt is known for its nutritional, therapeutic and functional properties. The present study was undertaken to standardise fruit pulp based yoghurts and to enrich the standardised products with functional ingredients like garden cress seed and flax seed. The study also envisaged to evaluate the organoleptic, physico chemical, nutritional and keeping qualities of the standardised products. Fruit pulp based yoghurts (FPBY) were prepared using locally available fruits such as sapota, guava, jackfruit (Koozha type), banana (Palayamkodan) and papaya. Twenty six treatments were evaluated for various organoleptic qualities and was compared with 100 per cent milk yoghurt (control). In different treatments tried for the preparation of FPBY, the mean scores for different quality attributes showed a decreasing trend with increase in the quantity of fruit pulps. Yoghurts prepared by incorporating 10 per cent fruit pulp was selected as the most acceptable treatment from all FPBY. Physicochemical properties like moisture and pH decreased during storage and a gradual increase in acidity, syneresis, curd tension and viscosity was observed in FPBY. In the selected products TSS, reducing sugar, total sugar, energy, carbohydrate, lactose, fat, vitamin C and iron content decreased during storage. Protein content of freshly prepared control yoghurt was 4.59 per cent and on 15th day of storage it decreased to 3.35 per cent. The protein content varied from 3.76 to 2.71 per cent in SPBY (Sapota pulp based yoghurt), 3.23 to 2.61 per cent in GPBY (Guava pulp based yoghurt), 3.91 to 3.08 per cent in BPBY (Banana pulp based yoghurt), 4.42 to 3.22 per cent in JPBY (Jackfruit pulp based yoghurt) and 3.23 to 3.24 per cent in PPBY (Papaya pulp based yoghurt) in initial and at the end of storage respectively. Vitamin A and vitamin C content was found to be increased with incorporation of fruit pulp. The highest calcium content was found to be in control (78mg/100g) and a slight decrease in calcium content was observed among FPBY. A slight increase in iron and potassium content was observed in FPBY compared to control. The highest potassium content was observed in BPBY with an initial content of 83.25 to 83.05 mg/100g at the end of storage. The selected FPBY was incorporated with garden cress seeds (GCS) and flax seeds (FS) at 0.5 per cent and 2 per cent level, respectively. The highest total organoleptic scores were attained for control (51.67) which was incorporated with garden cress seeds. This was followed by GPBY (48.45), SPBY (48.33), JFPBY (47.81), BPBY (46.73) and PPBY (43.72). In flax seeds incorporated yoghurts the highest organoleptic score was attained for control (40.78) which was followed by GPBY (40.15), SPBY (40.14), BPBY (39.94), PPBY (39.82) and JFPBY (39.78). Incorporation of 0.5 per cent garden cress seeds and 2 per cent flax seeds increased the protein content from 4.59 per cent to 4.78 and 4.93 per cent respectively. Incorporation of functional ingredients increased the fat, iron, calcium and potassium content in all yoghurts. During storage, E coli and coliform bacteria were not detected in all yoghurt samples. Yeast and fungi was not detected up to 10th day of storage and at 15th day of storage the presence of yeast and fungi were observed among all the selected yoghurt samples, indicating a shelf life of ten days. The cost of production of plain yoghurt was Rs. 13.50/100 ml and for FPBY it varied from Rs. 17.00 to 20.00/100 ml. Incorporation of functional ingredients increased the cost of production from Rs. 17.16 to 21.00/100 ml. The standardised products are suitable for commercialisation and diversification. Milk based functional food products will be a boon to the dairy food industry.